The Effect of Biochar Particle Size on Biogas Production Using Bread Waste Substrate - Sugiarto, Yusron; Wijayanti, Ulimaz Rahma; Sunyoto, Nimas Mayang Sabrina; Maharsih, Inggit Kresna; Andriani, Ria Dewi; Anugroho, Fajri (Universitas Brawijaya, 2023)
The effect of biochar supplementation with different particle size on biogas production in two-stage anaerobic digestion of white bread waste was carried out on a laboratory scale using a 100 mL bioreactor. The supplementation of biochar variations with particle sizes <63 µm, <125 µm, <149 µm, <250 µm, and <500 µm and the addition of different biochar concentration of 5 g/L, 15 g/L, and 25 g/L were investigated to obtain optimal concentrations. Mixed cultures were incubated at 35 °C for 40 days. Daily gas production, pH and Chemical Oxygen Demand (COD) were measured using the daily water displacement method. The results showed that the particle size of biochar < 500 µm with a biochar concentration of 5 g/L increased biogas production by 60% and resulted in gas accumulation of 4,240.03 mL/L. CH4, It has proven that biochar increased pH in the mixture. COD concentration decreased from 9,670 mg/L to 1,640 mg/L.